(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Adenomyosis is a common gynecological problem characterized by the growth of endometrial glands and stroma within the myometrium. Previously, the definitive diagnosis of adenomyosis was made through histopathology after a hysterectomy. However, in the last two decades, several uterine-sparing treatment options have emerged, including High-Intensity Focused Ultrasound (HIFU), which has become a promising option. HIFU is a non-invasive local thermal ablation technique that can be performed via ultrasound or MRI guidance. Additionally, “Laparoscopic uterine artery occlusion with uterus sparing pelvic plexus block and partial adenectomy for adenomyosis” has become a popular option. While conventional adenomyomectomy carries a high risk of recurrence and uterine rupture, some novel surgical techniques have been described to mitigate these complications and preserve future fertility. There are also “new surgical techniques of laparoscopic resection of adenomyoma under real-time intraoperative ultrasound elastography guidance”. Diagnostic imaging techniques such as transvaginal ultrasound, MRI, and hysteroscopic evaluation have revolutionized the diagnosis of adenomyosis and opened up possibilities for conservative treatment options. Hysteroscopy can be used for direct visualization and biopsy collection, though it is not the first-line treatment option. With the increasing incidence of adenomyosis and the desire for fertility preservation among younger patients, there is a growing need for effective uterine-sparing treatments. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 55-58